In Vitro Anti-Candida Activity of Lidocaine and Nitroglycerin: Alone and Combined - Ana Palmeira-; Ana Rita Ramos; Carlos Gaspar; Rita Palmeira-; Paula Gouveia; José Martinez- (Hindawi Limited, 2012)
The aim of this work was to study the anti-Candida activity of lidocaine and nitroglycerin alone and in combination. Ten Candida strains were included, corresponding to 1 collection type strain (ATCC 10231) and 9 clinical isolates: 4 C. albicans, 2 C. glabrata, 1 C. tropicalis, 1 C. krusei, and 1 C. parapsilosis. The CLSI reference M27-A3 micromethod was used to determine the anti-Candida activity of the drugs alone; minimal inhibitory and lethal concentrations were determined. The classic checkboard technique was used to determine the activity of combined drugs. Lidocaine fungicidal effect was dosedependent. Nitroglycerin exhibited a higher effect. The drugs combination resulted in a reduction of the inhibitory concentration, corresponding to an additive effect. In conclusion, both drugs exhibited an interesting anti-Candida activity. The combination of lidocaine with nitroglycerin was shown to have an additive effect against Candida spp., predicting the interest to include, in the future, these drugs in a new delivery system for the treatment of mucocutaneous candidosis.